German Learning for Students with Special Needs at SMAN 9 Malang - Gading Eko Nugroho (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
This study aims to describe the process of learning German for student with special needs at SMAN 9 Malang, to identify problems faced by teacher in the process of learning German in student with special needs at SMAN 9 Malang, and to identify the efforts made by the teacher to overcome the problems which arise in the learning process. This study used qualitative-descriptive research method. The results of this study indicated that the process of learning German at SMAN 9 Malang implemented a full inclusion learning model. Materials, media, and evaluation sheets given to student with special needs were the same as those given to regular students. Problems faced by teacher during the learning process were the problem of achieving learning goals, behavior, concentration, and motivation. The teacher's efforts to overcome the problem of achieving learning objectives and material problems are by simplifying the delivery of material with the availability of special guidance teacher. In addition, German teacher assisted by a special guidance teacher would always guide and lead student with special needs with the aim of controlling behavior to be enthusiastic in participating in German learning activities. Keywords: Learning, German, Student with Special Needs